The Use of Social Media in Improving English Speaking Skills (Literature Review 2014 – 2024) - Azizah, Siti; Supeno, Bana (MultiTech Publisher, 2024)
This study aims to provide a brief overview of the of the state of importance of the topic of the use of social media in improving English speaking skills, to identify patterns and trends in the effectiveness of social media for English speaking skills, and to draw conclusions about the overall effectiveness of social media in improving English speaking skills. The research method used was a literature review with a systematic review approach. The findings suggest that social media might be a useful tool for developing English-speaking skills by highlighting its positive qualities. To fully realize its potential, it should be combined with structured language instruction and feedback from qualified teachers or native speakers. In addition, some recommendations should be implemented in practice.